Hydrologic response: Kaho'olawe, Hawaii - Wahlstrom, Erik; Loague, Keith; Kyriakidis, Phaedon (My University, 1999)
The results of a series of physically-based numerical simulations of hydrologic response to large rainfall events on the Kaho'olawe island in Hawaii are presented. An event-based rainfall-runoff and erosion model, called KINEROS, was applied in a geographic information system (GIS) framework, to make quantitative and distributed estimates of infiltration, Horton overland flow generation, and erosion. A digital elevation model was used to delineate individual catchments across the island, and define areas of uniform slope within each catchment. A Landsat MSS scene of the island was also used to classify it into three distinct landcover categories via the normalized difference vegetation index.
Keywords: Groundwater flow; Catchments; Hydrologic model